Developing student writing in higher education: digital third-party products in distributed learning environments. Issue 5 (3rd July 2020) - Benzie, Helen Joy; Harper, Rowena
ABSTRACT: Academic literacies research emphasizes the importance of social context for understanding student writing development in higher education. In particular, students' choices of textual practices are shaped by perceptions of disciplinary norms and institutional expectations. In contemporary online learning environments, however, student writing is increasingly guided by advice from digital products – referred to in this paper as 'third-party products'. These are developed by commercial providers external to students' disciplines and institutions and include machine-based tools for analyzing texts, content-based courses on writing, and person-based services connecting students to writing tutors via online platforms. These products appear to offer universities the opportunity to outsource the task of developing student writing, however, they position writing as a technical process and elide the role of social context in determining what 'good' writing is. This paper locates third-party products within theories of academic writing, discussing implications for student writing development in 'distributed' university learning environments.